Analysis of the Induction and Wake Evolution of an Offshore Floating Wind Turbine - Matthew Lackner; Thomas Sebastian (Energies, 2012)
The degrees-of-freedom associated with offshore floating wind turbines (OFWTs) result in a more dynamic flow field. The resulting aerodynamic loads may be significantly influenced by these motions via perturbations in the evolving wake. This is of great interest in terms of OFWT design, placement and simulation. This study presents free vortex wake method (FVM) simulations of the NREL 5-MW wind turbine of a variety of platforms, operating in a range of wind speeds synthesized platform motion time series. Motion-induced wake perturbations are observed to affect induction. Transitions between windmill and propeller states are also observed.